1996
DOI: 10.1021/jp9602888
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Reactivity of NO and N2O on Cu{110}:  Combined RAIRS and Molecular Beam Studies

Abstract: The interaction of NO with Cu{110} is complex and is strongly dependent on both coverage and temperature. When Cu{110} is exposed to NO in the temperature range 40-85 K, initial adsorption leads to the presence of molecular NO on the surface. With further exposure this is replaced by the dimeric (NO) 2 species and N 2 O. Below 60 K, subsequent adsorption leads to the formation of multilayers of (NO) 2 . A detailed molecular beam study shows that adsorption is accompanied by the appearance of a range of gaseous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
73
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 25 publications
(62 reference statements)
7
73
0
Order By: Relevance
“…1 direction and thus is assigned to bent NO with the axis tilted along [001], that was previously observed by vibrational spectroscopies [10,18]. The dark image reflects that the 2 Ã molecular resonance is no longer retained for the bent species, as confirmed by its disappearance in the STS recorded over the depression [dashed curve in Fig.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…1 direction and thus is assigned to bent NO with the axis tilted along [001], that was previously observed by vibrational spectroscopies [10,18]. The dark image reflects that the 2 Ã molecular resonance is no longer retained for the bent species, as confirmed by its disappearance in the STS recorded over the depression [dashed curve in Fig.…”
supporting
confidence: 59%
“…On these surfaces, covalent interaction could contribute between NO molecules via the overlap of the ''active'' 2 Ã molecular orbitals. Actually, dimerization of NO has been observed in the submonolayer regime on Cu [9,10] and Ag [11,12]. Nevertheless, it remains yet to be clarified if the 2 Ã molecular state is indeed present for an isolated NO monomer and then how it evolves as NO forms a dimer.…”
mentioning
confidence: 99%
“…Similar observations have been made by Jorgensen et al for coadsorbed hydroxyl and oxygen on Ag-{110}, for which it was found that atomic O stabilizes the hydroxyl groups via attractive lateral interactions that can extend for up to twice the lattice distance. 20 The production of oxide rings, Ag 12 15 Spontaneous ring formation results from the heating of the (NO) 2 adlayer to 130 K, but the low temperature does not allow sufficient diffusion, for the formation of an equilibrated surface with p(4×4)-O islands and atomic subsurface O c . 15 At higher temperatures (>400 K), these rings would become unstable and break up into a two-phase system composed of islands of p(4×4)-oxide and subsurface atomic O c .…”
Section: Desorption Of N 2 O (A) and Formation Of Silver Oxide Ring Rmentioning
confidence: 99%
“…The N 2 O is formed from the reaction of N atoms with NO, most likely at the step edges. Most of the N 2 O that is formed then immediately dissociates to form gas 33 Due to the presence of the step sites, it might be expected that an even larger proportion of the N 2 O might dissociate on Pt͕211͖. The O atoms which would result from the decomposition of N 2 O would bind strongly to the step sites on Pt͕211͖ as shown previously.…”
Section: Resultsmentioning
confidence: 77%